Tradição um caminho na contramão da história?: Contribuições para o esclarecimento do conceito de tradição na obra Wahrheit und Methode de Hans-Georg Gadamer - Santiago, Alberto Antonio (2009)
The text deals with hermeneutic and tradition. The problem dealt with is the concept of tradition, which comprised new elements throughout the centuries, conditioning its acceptance or its rejection. This works desires to punctuate a few moments in the last 500 years of western history, observing the reactions posed in light of the phenomenon of tradition, insofar as its concept would gain new shades. This search is extremely important to our current times, as shown by the still recent polemics between Gadamer and Habermas. The hypothesis of work is that the shades gained by the word tradition were expressed by Gadamer in Wahrheit und Methode with the German words Tradition and Überlieferung. To gasp such nuance is of the utmost importance for the understanding of a concept of tradition that can survive in our present world. The Methodes applied were the bibliographic review and the semantical analyses. The search for a solution follows, in the first chapter, the German philosopher Hans-Georg Gadamer s proposal of rehabilitating tradition, starting from two paths: Aristotle s ethic and Philosophy of Language. It also presents objections from Jürgen Habermas and the Frankfurt School, as well as Gadamer s answers. In the second chapter, the text presents a few considerations concerning the swing between acceptance and rejection of tradition during the last 500 years of western history. It looks back on the formation of Christian tradition emphasizing the patristic period; it comments on the reformer s retort and the elaboration of the first hermeneutic; it presents Enlightenment s objections with the creation of the prejudice against prejudice, up until the summit with the French Revolution in its intent of renewing all things in light of reason. It ends with Romanticism s timid reaction which, nevertheless, cannot overcome Enlightenment s objections to tradition. In the third chapter, the text presents a detailed semantical analysis on the use of the words Tradition and Überlieferung in the work Wahrheit und Methode (Truth and Method) by Hans-Georg Gadamer. The intention is to show that the distinction in the use of either word confers a particular comprehension to the work and this allows one to bypass certain common objections to tradition. The concept of tradition rests enriched in its range and comprehension, but not as restricted as the author would like it to be